Conceptual Research Model for Studying Students’ Entrepreneurial Competencies - Zdolšek Draksler, Tanja; Širec, Karin (Naše gospodarstvo/Our economy, 2022)
The literature review shows a lack of research on the impact of entrepreneurship education on entrepreneurial competencies in relation to entrepreneurial intentions. Further development of the field is needed, but, because of the shortage of suitable research models or because they only partially cover the complex area of entrepreneurial competencies, the purpose of this article is the formulation of a new, updated research model (based on the existing models). Thus, theoretical research of entrepreneurial competencies based on the competence study has been performed. Through in-depth analysis of existing entrepreneurial competencies research models, a congregated hybrid research model is proposed. A new conceptual research model for studying the impact of entrepreneurship education on entrepreneurial competencies in relation to entrepreneurial intentions has been developed. The model will serve for empirical testing of investigated phenomena. The original contribution is in the formulation of a unique research model and the construction of a customized measuring instrument for studying the phenomena of entrepreneurship education impact on entrepreneurial competencies and entrepreneurial intentions.